Wreck of the Japanese ship Tenyo Maru, sunk during World War II - Meigan, Tom, 1931- (1955)
The Tenyo Maru was a converted mine layer used by the Japanese Navy during World War II. On 10 March 1942 the Tenyo Maru was extensively damaged by US aircraft and was subsequently beached on the reef off Lae. Since this photograph was taken, the Tenyo Maru has sunk.
Title from acquisition documentation.
This is a copy made by the National Library of Australia from an original in private ownership.
Part of collection: Papua and New Guinea, 1955-1960.
"The wreck was located on a reef at the end of the Lae airstrip, but slid into deeper waters during an earth tremor in the late 1960s."--Acquisition documentation.
Also available online
Keywords: Tenyo Maru (Minelayer) -- Photographs; Japan. -- Kaigun -- Photographs; Minelayers (Ships) -- Japan -- Photographs; Minelayers (Ships) -- Papua New Guinea -- Lae -- Photographs; Shipwrecks -- Papua New Guinea -- Lae -- Photographs